Technology mediation in child sexual exploitation and abuse in Africa and Asia - Sakshi Ghai; Matti Vuorre; Daniel Kardefelt-Winther; Amanda M. Ferguson; Sebastian Kurten; Sonia Livingstone; Andrew K. Przybylski; Amy Orben (Nature, 2026)
Abstract As digital access expands rapidly among children worldwide, technology-facilitated child sexual exploitation and abuse (CSEA), including online grooming, sexual solicitation, non-consensual image sharing and sexual extortion, has emerged as urgent yet underexamined category of digital harms 1 . Despite growing policy attention to online safety, evidence remains limited, particularly in low- and middle-income countries, where most of the world’s children live 2 . We analysed nationally representative survey data from 11,912 children aged 12–17 years across 12 countries in eastern and southern Africa and Southeast Asia, collected through the Disrupting Harm project in 2020–2021. We found that one in six internet-using children experienced at least one form of technology-facilitated CSEA, equivalent to over 10 million children. Despite this scale, many experiences went undisclosed, pointing to disclosure as a critical pathway for protection in the digital age. When children did disclose, they relied primarily on informal channels, especially friends, rather than formal reporting mechanisms such as police or helplines. Using Bayesian hierarchical models accounting for cross-country heterogeneity, we find that older children were less likely to disclose, whereas enabling parental mediation of online activities and children’s knowledge of where to seek help after sexual harassment or assault were associated with higher rates of disclosure. These findings provide population-level evidence to inform prevention and response across low- and middle-income countries, where coordinated action by policymakers, law enforcement and technology companies is urgently needed to protect all children.